Higher pulsatile index in carotid arteries is associated with adverse outcomes in patients treated by left ventricular assist device. (25th November 2020) - Tucanova, Z; Wohlfahrt, P; Ivak, P; Netuka, I; Pitha, J
Abstract: Introduction: Better understanding of vascular changes in patients after implantation of left ventricular assist devices (LVAD) is important to understand and prevent complications of this therapy. Currently, there is substantial lack of data regarding the impact of changes in carotid territory on clinical events in this population. Our aim was to analyze the association between carotid flow patterns and atherosclerotic changes with serious clinical events after LVAD implantation in a prospective single-center study. Methods: Eighty five patients were included (Heart mate II, n=34; Heart mate 3, n=51; mean age 55±15 years; 13 women). Pulsatile and resistance indexes were calculated and atherosclerotic changes (Belcaro score) were assessed using triplex ultrasound at the 3rd and 6th month after LVAD implantation. Basic clinical and laboratory data were also included into the analyses. The median follow-up time was 982 days [IQR 472–1431]. Results: Pulsatile and resistance index significantly increased between 3rd and 6th month (p=0.036 and p=0.012, respectively). Belcaro score did not change significantly. During the follow-up, 17 patients died, 4 due to stroke. Another 4 patients suffered from non-fatal stroke. Pulsatile index measured at 3rd month was associated with an increased risk of composite outcome of stroke, GIT hemorrhage and all-cause mortality (HR 10.6, 95% CI 2.0–55.2, p=0.005) only in the group of HeartMate 3 patients, while not in patients with HeartMate II (HR 0.96, 95% CI 0.07–12.4, p=0.97), p for interaction between groups 0.04. Association between pulsatile index and the risk of adverse events in patients with HeartMate 3 remained significant after adjustments for age, cause of heart failure and INTERMACS score. Conclusion: Among patients after LVAD implantation, assessment of carotid flow patterns, pulsatile index in particular, may identify individuals at increased risk of serious clinical complications. Future studies are needed to understand mechanisms leading to increase flow pulsatility in this population. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): Ministry of Health of the Czech Republic